Synthesis and Biological Activity of Substituted Urea and Thiourea Derivatives Containing 1,2,4-Triazole Moieties - KAYMAKÇIOĞLU, BEDİA (MDPI, 2013)
A series of novel thiourea and urea derivatives containing 1,2,4-triazole moieties were synthesized and evaluated for their antifungal and larvicidal activity. Triazole derivatives 3a-e and 4a-e were synthesized by reacting thiocarbohydrazide with thiourea and urea compounds 1a-e and 2a-e, respectively, in a 130-140 degrees C oil bath. The proposed structures of all the synthesized compounds were confirmed using elemental analysis, UV, IR, H-1-NMR and mass spectroscopy. All compounds were evaluated for antifungal activity against plant pathogens, larvicidal and biting deterrent activity against the mosquito Aedes aegypti L. and in vitro cytotoxicity and anti-inflammatory activity against some human cell lines. Phomopis species were the most sensitive fungi to these compounds. Compounds 1b, 1c, 3a and 4e demonstrated selectively good activity against Phomopis obscurans and only 1b and 4e showed a similar level of activity against P. viticola. Compound 3d, with a LD50 value of 67.9 ppm, followed by 1c (LD50 = 118.8 ppm) and 3e (LD50 = 165.6 ppm), showed the highest toxicity against Aedes aegypti larvae. Four of these compounds showed biting deterrent activity greater than solvent control, with the highest activity being seen for 1c, with a proportion not biting (PNB) value of 0.75, followed by 1e, 2b and 1a. No cytotoxicity was observed against the tested human cancer cell lines. No anti-inflammatory activity was observed against NF-kappa B dependent transcription induced by phorbol myristate acetate (PMA) in human chondrosarcoma cells.
Keywords: thiourea; urea; 1,2,4-triazole; synthesis; fungicide; plant pathogens; larvicides; mosquitoes; anti-inflammatory; cytotoxicity; IN-VITRO; ANTIMICROBIAL EVALUATION; AMPHOTERICIN-B; DESIGN; ANTIBACTERIAL; ITRACONAZOLE; VORICONAZOLE; FLUCONAZOLE; TRIAZOLE; ANALOGS